ANALISIS TENAGA KERJA TERHADAP KEGIATAN SEKTOR EKONOMI DALAM PERENCANAAN KOTA KABUPATEN KARIMUN - Tri Gamela Saldy; Dina Fara Waidah; Tiuridah Silitonga; Panji Pangestu (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Labor is every person who is able to do work to produce goods or services to meet needs. Economic sector activities and urban planning have important relationships in the development plan. Gross Regional Domestic Product (GRDP) is one of the references that can be used in determining the ability of economic resources and shows the rate of economic growth so that the economic base sector of a region is known. The problem raised in this study is that urban development planning in Karimun Regency is not in accordance with the activities of the economic sector which is the base sector.The research method used in this study is the LQ (Location Quotient) Analysis which is to analyze the potential or base sector in the economy in an area,  namely the entire workforce and GRDP according to the main employment sector and the sample, which is based on labor data in nine main employment sectors and GRDP at current prices with data for 2011-2015 for the Karimun Regency and Riau Islands Province. The results obtained in this study are the first Agricultural sector plays a role as a base sector in economic growth in Karimun Regency, then the second base sector is the Construction sector.  Keywords: Labor,  economic sector, city planning, GRDP, LQ Analysis